Antioxidant and antibacterial activity in fresh leaves of plecranthus amboinicus - Nor Asmira Abu Bakar (2014)
This research intent to evaluate antioxidant and antimicrobial potential of methanolic extract of Plecranthus amboincus as a natural source of antioxidant and antibacteria. Fresh leaves samples were grinded and extracted by soaking in 200 ml of 100% methanol for 42 hours. The extract were filtered using Whatman No. 1 filter paper and muslin cloth, then concentrated in Heidolph rotary evaporator at 45°C under reduced pressure, yielding gummy mass for P.amboinicus. Next, scavenging assay was used for antioxidant test and paper diffusion method was used for antimicrobial activity against two types of pathogens; E.coli and S.aureus. The antioxidant properties of methanolic extract was proven since positive results were obtained from DDPH scavenging assay which gave IC₅₀ value of 20.22µg/ml. Methanolic extract of P. amboinicus inhibited S. aureus which is gram positive bacteria but showed no inhibition for E. Coli; gram negative bacteria. The results demonstrated the significant presence of antioxidant and antibacterial properties in methanolic extract of P. amboinicus. This research found that high content of antioxidant in this plant can be commercialized as effective natural remedies, culinary additive and aromatherapy.